2022
DOI: 10.1038/s41598-022-26164-4
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of soil nutrition on floral traits, pollinator attraction, and fitness in cucumbers (Cucumis sativus L.)

Abstract: Annual plants allocate soil nutrients to floral display and pollinator rewards to ensure pollination success in a single season. Nitrogen and phosphorus are critical soil nutrients whose levels are altered by intensive land use that may affect plants’ fitness via pollinator attractiveness through floral display and rewards. In a controlled greenhouse study, we studied in cucumbers (Cucumis sativus) how changes in soil nitrogen and phosphorus influence floral traits, including nectar and pollen reward compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…For example, Brassica napus L. (Brassicaceae) pollen can contain over 25% lipids when the exine is disrupted prior to analysis (Evans et al 1991, Lau et al 2022). Recent research have emphasized the importance of the ratio of proteins to lipids (P:L) in pollen, which can be a driving factor for bee pollen preferences (Vaudo et al 2015, 2016, 2020, 2022). Lipids shown to be essential for bees include fatty acids (oleic acid, omega 6 and omega 3 fatty acid) and phytosterols.…”
Section: Bee Biology and Nutritional Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Brassica napus L. (Brassicaceae) pollen can contain over 25% lipids when the exine is disrupted prior to analysis (Evans et al 1991, Lau et al 2022). Recent research have emphasized the importance of the ratio of proteins to lipids (P:L) in pollen, which can be a driving factor for bee pollen preferences (Vaudo et al 2015, 2016, 2020, 2022). Lipids shown to be essential for bees include fatty acids (oleic acid, omega 6 and omega 3 fatty acid) and phytosterols.…”
Section: Bee Biology and Nutritional Requirementsmentioning
confidence: 99%
“…Intensive soil management used to manage weeds, such as tilling, can disrupt soil structure that had been established over time. Such negative impacts on the soil can affect floral traits that influence pollinator attraction and have implications on both pollinator health and crop yield (David et al 2019, Dai et al 2022, Filipiak et al 2022b, Vaudo et al 2022). Skewed nutrient ratios in the soil can affect the total number of flowers and resource nutritional quality and quantity (Vaudo et al 2022, Russo et al 2023).…”
Section: The Changing Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…50% of their nitrogen and upwards of 90% of phosphorus from associations with AMF (Bennett & Groten, 2022). Nitrogen and phosphorus are critical to flower production and display (White & Hammond, 2008); the availability of these soil nutrients has previously been shown to positively impact the size of floral traits including floral display, nectar volume, and pollen count (Burkle & Irwin, 2009; Vaudo et al ., 2022). In a study of the impacts of inoculation with the AMF Glomus etuniacatum on the herbaceous annual Abutilon theophrasiti , Lu & Koide (1994) found that AMF inoculation in nutrient‐poor soils was associated with a dramatic increase in the number of flowers produced, a greater proportion of flowers setting fruit, longer total flowering duration, earlier flowering, and more seeds per fruit.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the impacts of inoculation with the AMF Glomus etuniacatum on the herbaceous annual Abutilon theophrasiti , Lu & Koide (1994) found that AMF inoculation in nutrient‐poor soils was associated with a dramatic increase in the number of flowers produced, a greater proportion of flowers setting fruit, longer total flowering duration, earlier flowering, and more seeds per fruit. Furthermore, a recent study reported that increasing soil N and P concentrations lead to floral trait changes that resulted in increased visitation by bumblebees to cultivated cucumber plants (Vaudo et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%